Factors Related To The Incidence Of Hypertension In 20-44 Years Of Age In The Work Area Uptd Community Health Center Sp-1 Kalibumi, Nabire Regency - Norinda Jikwa; Nur Susan Iriyanti Ibrahim; Alfred D Lambey (International Journal of Health and Social Behavior, 2025)
Hypertension is one of the most common cardiovascular diseases and is suffered by many people. Based on Southeast Asian data, hypertension causes around 8 million deaths each year, with cases in Southeast Asia around 1.5 million deaths due to hypertension. Data from the Work Area of the SP 1 Kalibumi Health Center UPTD, the incidence of hypertension in 2023 was 116 people aged 20-24 years. Objective: to determine the factors associated with the incidence of hypertension at the age of 20-44 years in the Work Area of the SP-1 Kalibumi Health Center UPTD, Nabire Regency. Method: This type of research is quantitative using a cross-sectional study approach, conducted in the work area of the SP-1 Kalibumi Health Center UPTD, Nabire Regency. A sample of 54 respondents aged 20-44 years who met the inclusion and exclusion criteria. Data processing was carried out using SPSS version 16. Results: The results of the Chi-Square statistical test obtained a p-value = 0.00 for the diet variable, p-value = 0.07 for the physical activity variable, p-value = 0.34 for the smoking habit variable, and p-value = 0.06 for the family history variable. Conclusion: The variables related to the incidence of hypertension are diet, while physical activity, smoking habits, and family history have no relationship. Suggestion: The community can regulate and maintain their diet to avoid hypertension. For further research, observe other variables for the incidence of hypertension.